Proximate and ultimate determinants of clutch size in Anatidae - Johnsgard, Paul A (Wildfowl, 1973)
A review of Anatidae clutch-size data and an analysis of David Lack’s hypothesis that food availability to the female around the time of her nesting can account for the evolution of average waterfowl clutch-sizes suggest several additions to or modifications of his theory. First, in contrast to Lack’s suggestion, proximate factors do influence anatid clutch-sizes and result in measureable seasonal, yearly and perhaps also interpopulational variations in these. Secondly, indirect evidence suggests that several factors in addition to average food supplies may have influenced clutch-size evolution. These include needs for efficient partitioning of energy reserves between the incubating female and her eggs, dangers of pre-incubation clutch losses in those species that are unusually susceptible to nest predation, and decreasing parental effectiveness as well as possible decreased available optimum breeding periods associated with increases in clutch-sizes. Several or all of these may have placed upper limits on anatid clutch-sizes independently of or in conjunction with food supply effects.